Effect of Nutritional Restriction on the Hair Follicles Development and Skin Transcriptome of Chinese Merino Sheep - Xuefeng Lv (Animals, 2020)
The high concentration of secondary branched wool follicles is a distinctive feature of the Merino sheep. At present, the molecular control of the development and branching of secondary wool follicles (SF) remains elusive. To reveal the potential genes associated with the development of hair follicles, we investigated the characteristics of prenatal and postnatal development of wool follicles, and the transcriptional expression profile in fetuses/lambs from dams under either maternal maintenance or sub-maintenance (75% maintenance) nutrition. The density of SF and the ratio of SF to primary wool follicles (PF) were reduced (p < 0.05) in fetuses from day 105 to 135 of gestation under sub-maintenance nutrition. Differentially expressed genes were enriched in the binding, single-organism process, cellular process, cell and cell part Gene Ontology (GO) functional categories and metabolism, apoptosis, and ribosome pathways. Four candidate genes, SFRP4, PITX1, BAMBI, and KRT16, which were involved in secondary wool follicles branching and development, were identified. Our results indicate that nutritional intervention imposed on pregnant ewes by short-term sub-maintenance nutrition could provide a strategy for the study of wool follicle development. Overall insight into the global gene expression associated with SF development can be used to investigate the underlying mechanisms of SF branching in Merino sheep.